The Impact of Teacher-Initiated Activities on Identifying and Verbalizing Ways of Metacognitive Monitoring and Control in Six-Year-Old Children - Ona Monkeviciene; Jelena Vildziuniene; Galina Valinciene (Research in Social Sciences and Technology, 2020)
The qualitative research presented in this article attempts to show the impact of teacher-initiated activities on six-year-old children’s metacognitive monitoring and control abilities. The metacognitive model is discussed, research findings that substantiate the development of separate components of metacognitive regulation are analyzed, and the educational ways that promote metacognitive development in children are systematized. The outcomes of the research show that teacher-initiated activities stimulate and encourage children to find and apply more diverse ways of metacognitive monitoring and control. After teacher-initiated activities, the target group children demonstrated, identified, and verbalized the following ways of acting and learning that had not been noticed in their self-initiated activities in the area of metacognitive monitoring, namely, thinking while doing, modelling, acting by scheme/without a scheme, and activity by self-created strategies. In the area of metacognitive control, the children showed the ability to challenge themselves to do better than before, think and do as a continuous, unbroken control and implementation process, and control performance consistency.